Essays on economics of education : higher education accountability and major-job match returns - Machado, Anaely da Silva (2022)
Tese (doutorado) — Universidade de Brasília, Faculdade de Administração, Contabilidade, Economia e Gestão de Políticas Públicas, Departamento de Economia, Brasília, 2022.